2011
DOI: 10.1177/1470357211398447
|View full text |Cite
|
Sign up to set email alerts
|

Cartoon drawing as a means of accessing what students know about HIV/AIDS: an alternative method

Abstract: Combating the spread of HIV/AIDS in Uganda has involved massive public education campaigns. One of the challenges of these campaigns has always involved the need to simultaneously respect and transcend cultural taboos around direct discussions about sexuality and sexual issues, particularly among youth. Research consistently shows that drawing, as a means of investigating what students know, has the potential to reveal students’ perceptions of given concepts and provides an alternative to predominantly languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…We find it most productive to place equal emphasis on each of the three sites, seeing them as inextricably connected and recursively relational to one another. Moreover, we take her core methodology as a constructive space for the integration of other visual methodologies (see, e.g., Kendrick & Jones, ; Mutonyi & Kendrick, ).…”
Section: Visual Methodologiesmentioning
confidence: 99%
“…We find it most productive to place equal emphasis on each of the three sites, seeing them as inextricably connected and recursively relational to one another. Moreover, we take her core methodology as a constructive space for the integration of other visual methodologies (see, e.g., Kendrick & Jones, ; Mutonyi & Kendrick, ).…”
Section: Visual Methodologiesmentioning
confidence: 99%
“…'s () report on the construction of multimodal dual‐language books, Marshall and Toohey's () research on the multimodal transformations of Punjabi children's family narratives, Lotherington and Chow's () study of the use of digital media to develop writing, and Naqvi's () documentation of use of multimodal dual‐language books in content areas. More broadly, researchers into human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) and health education have described how nonlinguistic modes have enabled a more substantial understanding of difficult knowledge and experience than linguistic modes alone (Mutonyi & Kendrick, ). In each case, the work of TESOL researchers has raised critical questions regarding the place of learners’ plurilingual resources within their multimodal repertoires, and how students’ repertoires might figure in language pedagogies.…”
Section: A Range Of Researchmentioning
confidence: 99%
“…This data collection and analysis was chosen for a number of reasons. First, participants were children and research has demonstrated that powerless or minority populations may be better able to express their perceptions through visual representations rather than through language (Mutonyi & Kendrick, 2011; Tracy & Malvini Redden, 2015). Second, drawing as a data collection method has been shown to elicit taken-for-granted assumptions of identity characteristics (Bell & Clarke, 2014), which aligns well with our research aims related to implicit constructions of identity.…”
Section: Methodsmentioning
confidence: 99%